From Wave Energy to Electricity: Functional Design and Performance Analysis of Triboelectric Nanogenerators - Lou, Ying; Li, Mengfan; Yu, Aifang; Zhai, Junyi; Wang, Zhong Lin (Nano-Micro Letters, 2025)
Triboelectric nanogenerators (TENGs) offer a self-sustaining power solution for marine regions abundant in resources but constrained by energy availability. Since their pioneering use in wave energy harvesting in 2014, nearly a decade of advancements has yielded nearly thousands of research articles in this domain. Researchers have developed various TENG device structures with diverse functionalities to facilitate their commercial deployment. Nonetheless, there is a gap in comprehensive summaries and performance evaluations of TENG structural designs. This paper delineates six innovative structural designs, focusing on enhancing internal device output and adapting to external environments: high space utilization, hybrid generator, mechanical gain, broadband response, multi-directional operation, and hybrid energy-harvesting systems. We summarize the prevailing trends in device structure design identified by the research community. Furthermore, we conduct a meticulous comparison of the electrical performance of these devices under motorized, simulated wave, and real marine conditions, while also assessing their sustainability in terms of device durability and mechanical robustness. In conclusion, the paper outlines future research avenues and discusses the obstacles encountered in the TENG field. This review aims to offer valuable perspectives for ongoing research and to advance the progress and application of TENG technology. Highlights: 1 Systematically expounding functional design of reported triboelectric nanogenerators (TENGs). 2 Conducting an extensive comparison of the power conversion efficiencies of TENGs in air and water wave environments. 3 Comprehensively assessing the existing challenges and delineating the future pathways for development.